Workforce Participation and Economic Empowerment of Women: An Order Logit Regression Approach - Mazumdar, Gautam; Sinha, Madhabendra; Kumar Banerjee, Amit; Ray Chaudhury, Anjan; Pratim Sengupta, Partha (International Journal of Psychosocial Rehabilitation, 2020)
The paper is an attempt to investigate the inter-linkage between the workforce participation and economic empowerment of women. To attain the sustainable development goal in a developing country like India, women’s empowerment has been identified as a vital fact in regard to addressing the issues of poverty, inequality, inclusive development of women, children, and society. Primary data was collected and analyzed from one of the progressive districts, Nadia, State West Bengal, India, using an ordered logit econometric model. The study observes four significant parameters and its influence upon women’s economic empowerment in relation to the prevailing patriarchal sociocultural environment. The findings of the study reveal that despite various efforts made to bring women to the forefront by giving access to opportunities to meet their aspirations, it is found that women have made strides and are empowered having access to resources, education, marriage, and living in urban localities, but women’s progress as a worker, self-employment, single, working in the informal sector, and rural areas seems to be at a snail’s pace. There is underutilization of women’s potential and their empowerment for coming forward and playing key roles as business leaders, entrepreneurs, and professionals.